Hubungan Tingkat Serangan Ulat Kipat (Cricula Trifenestrata) terhadap Hasil Mete - Rina Siswanti; Supriyadi Supriyadi; Subagiya Subagiya (Agrotechnology Research Journal, 2017)
Cricula  trifenestrata  Helfer  (Lepidoptera;Saturniidae) are  insect  pest  of  avocado,  walnuts,  and  cashews.  C. trifenestrata is most destructive insect pest of cashews, but there is no serious control by farmers. The questions about the effect of C. trifenestrata to cashew’s yield. This study aimed to determine the correlation and regression attack  degree of  C.  trifenestrata to  the  number of  flowers and  seeds produced by cashew. Research was conducted by a survey of 30 cashew plants with 6 samples unit at each plant. The parameters observed in this study were plant varieties, plant age, time appears caterpillar, caterpillar number, the attack rate, days to flowering, the number of bunches, flower, and seed. The data were analysed by the correlation and regression analysis. The results showed a positive correlation between the degree of caterpillar attacks to number of flowers and seeds. Increasing degree of attacks may increase the number of flowers and seeds.